JQUERY SEBAGAI KOMPONEN USABILITAS ANTARMUKA APLIKAS WEB - Irma Salamah; Muhammad Aris Ganiardi; RD Kusumanto (Universitas Catur Insan Cendekia (CIC) Cirebon, 2016)
Web applications are most widely used by the user in the cooperative information portal. This web application type is used as a communication tool to distribute information to the general public relating to the the organization or company. State Polytechnic Sriwijaya develop information portal that is used to distribute information related to academic activities in the form of announcements and news that happens in the State Polytechnic Sriwijaya. Portal of information held by the State Polytechnic Sriwijaya has not implemented the quality factor of reusability in Web application development cycle. The purpose of this research is to implement JQuery as the application of the quality factor of reusability at the Polytechnic of Sriwijaya information portal. JQuery is applied on the portal interface to allow users to use the information portal. Results obtained from this study that more information portal interesting and attractive. Keywords : JQuery, Usability, Web Aplicationexpectancy, social factor